Living with an Infected Planet COVID-19, Feminism, and the Global Frontline of Care - Krasny, Elke (X-Texte zu Kultur und Gesellschaft, 2023)
»We must declare war on the virus,« stated UN chief António Guterres on March 13, 2020, just two days after the WHO had characterized the outbreak of the novel Covid-19 virus as a pandemic. Elke Krasny introduces feminist worry in order then to develop a feminist cultural theory on pandemic frontline ontologies, which give rise to militarized care essentialism and forced heroism. Feminist hope is gained through the attentive reading of feminist recovery plans and their novel care feminism, with the latter's insistence that recovery from patriarchy is possible.